A Review of SARS-CoV-2 Genetic and Structure: Hot Cellular Targets for Virus Entry: Genetic and structure of COVID-19 - Torabizadeh, Mehdi; Ghobadi Dana, Vahid; Aghapour, Seyed Ali; Zibara, Kazem; Deris Zayeri, Zeinab; Rajaei, Elham (Archives of Medical Laboratory Sciences, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses several molecules such as angiotensin-converting enzyme 2 (ACE2), cluster of differentiation 26 (CD26), Ezrin, and Neuropilin-1 (NRP-1) for viral entry. In this review, the entire structural and genomic combination and the mechanism of virus entry, are discussed. This study might be useful for further drug design studies. SARS-CoV-2 neutralization allows the immune system to fight the virus before its entry. COVID-19 enters the host bloodstream by infecting endothelial cells via a cluster of differentiation 147 (CD147). SARS-CoV-2 not only uses ACE2 for its entry but also affects ACE-2 and its enzymatic activity on Ang II and bradykinin, it also imbalances the RAAS and bradykinin system and elevates the inflammation. High levels of bradykinin, cause nonproductive cough as the result of fluid extravasation and leukocyte recruitment to the lung. Accordingly, we suggest replicase transcriptase complex (RTC) and specific non-structural proteins (Nsps) such as Nsp7,8, Nsp10, Nsp12, and Nsp16 are perfect targets of study because RTC and Nsps are the golden elements in the maintenance of COVID-19 appearance and masking. Base on this evidence COVID-19 uses various receptors for its entry and it might block these receptors’ activity to evade the immune system and spread to other cells. *Corresponding Authors: Elham Rajaei, Email: elhamrj@gmail.com; ORCID: https://orcid.org/0000-0002-8231-0138 Please cite this article as: Torabizadeh M, Ghobadi Dana V, Aghapour SA, Zibara K, Deris Zayeri Z, Rajaei E. A Review of SARS-CoV-2 Genetic and Structure: Hot Cellular Targets for Virus Entry. Arch Med Lab Sci. 2021;7:1-9 (e15). https://doi.org/10.22037/amls.v7.34216